The Role of Job Engagement as a Mediator in the Influence Between Psychological Capital and Performance - Adipratama, Satria Muhammad (Universitas Ciputra Surabaya, 2022)
Several studies show that work engagement acts as a mediator between psychological capital and social support on performance (Bakker & Demeuroti, 2019). The aim of this researcher is to determine the role of work engagement as a mediator in the relationship between psychological capital and social support on performance. The subjects in this study were employees of PT. Adhibaladika Agung. From a total population of 311 employees, as many as 175 people were sampled in this study. The data collection technique used in this study was purposive sampling. The analysis technique in this study uses the SmartPLS program and before being analyzed, it is done first to check whether there are operational items that fail or not using Statistical Product and Service Solution (SPSS). The results of this study indicate that all variables have a significant influence or can also be called 7 of 7 accepted research hypotheses. In practice, the seven hypotheses that have been proven to be accepted and show a significant value will certainly be very useful as a reference for companies to increase psychological capital, social support, work engagement and employee performance. Each endogenous variable that wants to be improved is recommended with a different solution in aspects related to its endogenous variable or it can be concluded that t count from H1 is the Psychological Capital variable on Performance = 13.346 (solution: training), H2 is the Social Support variable on Performance = 5,382 ( solution: role model), H3 is Psychological Capital variable on Work Engagement = 3,308(solution: training), H4 is Social Support variable for Work Engagement = 2,397 (solution: role model), H5 is Work Engagement variable on Performance = 7,840 (solution : rewards and punishments). This research also proves that the JD-R Model is still valid today.